2008
DOI: 10.1007/s11842-008-9040-8
|View full text |Cite
|
Sign up to set email alerts
|

Forest Allocation Policy and Level of Forest Dependency of Economic Household Groups: A Case Study in Northern Central Vietnam

Abstract: A new forest policy of allocating forestland to individual households for management and development, has been applied in Vietnam since the early 1990s. This study was designed to examine how local forest-related people have used forestland and forest resources under the new policy, and to determine their level of dependency on forests. An upland forest-related community in northern central Vietnam, where the policy was introduced in 2002, was chosen as a case study. It was found that local residents in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Enhancement of community-based mangrove management: Since the early 1990s, forest policy of allocating forestland to forest-adjacent people for management and development has been applied in Vietnam (Quang and Noriko, 2008), but it has not been applied for mangrove forests. The issues of mangrove management and restoration are being considered as the key adaptation strategies for mitigating climate change and coastal storm damages in Thanh Hoa province.…”
Section: Implications For Sustainable Management Of Mangrove Forests mentioning
confidence: 99%
“…Enhancement of community-based mangrove management: Since the early 1990s, forest policy of allocating forestland to forest-adjacent people for management and development has been applied in Vietnam (Quang and Noriko, 2008), but it has not been applied for mangrove forests. The issues of mangrove management and restoration are being considered as the key adaptation strategies for mitigating climate change and coastal storm damages in Thanh Hoa province.…”
Section: Implications For Sustainable Management Of Mangrove Forests mentioning
confidence: 99%
“…This means that the economic value of mangrove forests is gradually decreasing due to the deforestation and degrading of mangrove forest. Levels of dependence on forest resources around the world among households with access to forests vary from 6 to 65% depending on the local circumstances [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Singh [43] in Bangladesh estimated that the contribution of non-timber forest products-NTFPs is 79% on average to the annual income of the collector's family.…”
Section: Dependence On Mangrove Forest Resourcesmentioning
confidence: 99%
“…Nevertheless, recently several studies have demonstrated that restrictions on the use of natural resources have negative behavior among the rural residents who rely on the forest for their livelihood, which creates a lot of hurdles for the management of forests [1][2][3][4][5]. The mountainous rural area resident's major source of income is from the forest resources; therefore, the economic incentive from forests directs rural residents toward deforestation [6][7][8][9][10][11][12]. Therefore, comprehensive attention is needed to understand the relationship between rural residents, economic incentives, and forest conservation.…”
Section: Introductionmentioning
confidence: 99%